THE FORM, MEANING AND FUNCTION OF ENGLISH LANGUAGE VARIATION: A SOCIOLINGUISTICS STUDY ON INDONESIAN REGISTER OF PHOTOGRAPHY - Zuhdah, Daumi Rahmatika; Firmonasari, Aprillia (Lire Journal (Journal of Linguistics and Literature), 2024)
This research aims to describe the linguistics form, meaning, and functions under the phenomenon of English language variation used by Indonesian photography enthusiasts. The influence of the English register in lexical categories mostly has undergone a shift in meaning. So, the analysis of English register in the photography context is fascinating to be examined. The method of this research is qualitative descriptive with a sociolinguistics approach. The data are restricted to words and phrases taken from the daily posting of the Facebook community group. The procedure of data collection was conducted by observing and noting the English register among photography enthusiasts. The data were analyzed based on the formation process, the contextual meaning, and identifying the functions and sociolinguistics aspects. This research revealed that the use of English as a foreign language in the conversation of Indonesian photography enthusiasts was largely formed in a 'word' that represent an intended meaning without explain it in a long way. Those terms are functioned to tell the information, experiences, facts, techniques in photography. The involvement of English in the photography register was assumed because several terms do not have equivalent sense in Indonesian language, so it better to use them in English. This research has also showed that the intention of using English in photography community as the characteristics to labeling their social identity, also increasing the speaker's social value, particularly in creating feelings of pride and prestige.